2016
DOI: 10.1038/srep24828
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged sleep restriction induces changes in pathways involved in cholesterol metabolism and inflammatory responses

Abstract: Sleep loss and insufficient sleep are risk factors for cardiometabolic diseases, but data on how insufficient sleep contributes to these diseases are scarce. These questions were addressed using two approaches: an experimental, partial sleep restriction study (14 cases and 7 control subjects) with objective verification of sleep amount, and two independent epidemiological cohorts (altogether 2739 individuals) with questions of sleep insufficiency. In both approaches, blood transcriptome and serum metabolome we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 91 publications
4
64
0
3
Order By: Relevance
“…Our findings regarding the influence of sleep quality on cholesterol levels is somewhat in concordance with other studies, which have found that poor sleep quality is associated with low HDL cholesterol60 ) , that sleep disturbances increase cholesterol levels61 ) , and that poor sleep quality increases risk of cardiovascular disease62 ) , although some studies have failed to find relationships between sleep quality and cholesterol levels26 ) . Similarly, multiple studies have found relationships between short sleep duration and cholesterol levels36 ) , including decreased HDL cholesterol37, 63 ) , increased LDL cholesterol25, 37 ) , and increased total cholesterol27, 29 ) . Other studies, none of which investigate long-haul truck drivers, have reported a curvilinear relationship between sleep duration and cholesterol levels26, 28 ) .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our findings regarding the influence of sleep quality on cholesterol levels is somewhat in concordance with other studies, which have found that poor sleep quality is associated with low HDL cholesterol60 ) , that sleep disturbances increase cholesterol levels61 ) , and that poor sleep quality increases risk of cardiovascular disease62 ) , although some studies have failed to find relationships between sleep quality and cholesterol levels26 ) . Similarly, multiple studies have found relationships between short sleep duration and cholesterol levels36 ) , including decreased HDL cholesterol37, 63 ) , increased LDL cholesterol25, 37 ) , and increased total cholesterol27, 29 ) . Other studies, none of which investigate long-haul truck drivers, have reported a curvilinear relationship between sleep duration and cholesterol levels26, 28 ) .…”
Section: Discussionmentioning
confidence: 92%
“…Endocrine functioning is impacted by sleep, which influences various metabolic processes, including lipid metabolism, by altering levels of hormones such as thyrotropin and cortisol34, 35, 36 ) . Sleep may also impact genes responsible for cholesterol transportation37 ) . Other mechanisms are more indirect.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, an experimental partial sleep restriction study of 14 subjects vs seven controls found that sleep restriction decreased the expression of genes encoding cholesterol transporters and increased expression in pathways involved in inflammatory responses, although circulating LDL decreased rather than increased in the sleep-restricted subjects 182. Metabolomic analyses in 2,739 adults also found that those reporting chronically insufficient sleep had lower circulating large LDL 182.…”
Section: Sleep Restriction and Sleep Architecture: Impact On The Metsmentioning
confidence: 99%
“…Very recently, an experimental partial sleep restriction study of 14 subjects vs seven controls found that sleep restriction decreased the expression of genes encoding cholesterol transporters and increased expression in pathways involved in inflammatory responses, although circulating LDL decreased rather than increased in the sleep-restricted subjects 182. Metabolomic analyses in 2,739 adults also found that those reporting chronically insufficient sleep had lower circulating large LDL 182. These findings suggest that while the impact on lipids is not necessarily apparent in acute sleep restriction, prolonged or chronic sleep deprivation can modify inflammatory and cholesterol pathways at the level of gene expression and serum lipoproteins, inducing changes that increase cardiometabolic risk.…”
Section: Sleep Restriction and Sleep Architecture: Impact On The Metsmentioning
confidence: 99%
“…Insufficient sleep contributes to an increased incidence of cardiovascular, metabolic and neurodegenerative diseases (Banks and Dinges, 2007; Mullington et al, 2009; Aho et al, 2016). Chronic restricted sleep also results in decrements in memory and performance (Alhola and Polo-Kantola, 2007; Goel et al, 2009).…”
Section: Discussionmentioning
confidence: 99%